2009
DOI: 10.1111/j.1600-079x.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the cGMP signaling pathway by melatonin in pancreatic β‐cells

Abstract: Melatonin influences the second messenger cyclic guanosine 3',5'-monophosphate (cGMP) signaling pathway in pancreatic beta-cells via a receptor-mediated mechanism. In the present study, it was determined how the regulation of cGMP concentrations by melatonin proceeds. The results provide evidence that melatonin acts via the soluble guanylate cyclase (sGC), as molecular investigations demonstrated that long-term incubation with melatonin significantly reduced the expression levels of the sGC mRNA in rat insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 51 publications
2
76
0
2
Order By: Relevance
“…High-throughput analysis of mRNA abundance with RNA sequencing (RNA-seq) has confirmed MT1 and MT2 expression in human islets, though equal abundance of transcript for each was reported in alpha and beta cells [107]. In the pancreatic islet, melatonin regulates a bevy of cellular activity and gene expression [108][109][110][111]. The observation that melatonin has sleep-promoting effects occurred almost in parallel with the discovery that this hormone had 'insulin-like' activity.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 74%
See 1 more Smart Citation
“…High-throughput analysis of mRNA abundance with RNA sequencing (RNA-seq) has confirmed MT1 and MT2 expression in human islets, though equal abundance of transcript for each was reported in alpha and beta cells [107]. In the pancreatic islet, melatonin regulates a bevy of cellular activity and gene expression [108][109][110][111]. The observation that melatonin has sleep-promoting effects occurred almost in parallel with the discovery that this hormone had 'insulin-like' activity.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 74%
“…Melatonin can also act through G i -coupled MT2 receptors in INS-1 cells to lower intracellular Ca 2+ levels [110,113], which is also predicted to reduce insulin secretion. Finally, melatonin can act through G q -coupled MT2 receptors to stimulate phospholipase C (PLC) and inositol triphosphate (IP3) activity [114], which is expected to boost insulin secretion.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…Recently, it became possible to identify the intracellular signal cascades of pancreatic beta cells that are melatonin-dependent. Our own previous investigations have shown that the MT 1 and MT 2 receptors of pancreatic beta cells are linked to adenylate cyclasecAMP [2], the phospholipase C inositol-1,4,5-triphosphate (IP 3 ) [12,13] and the guanylate cyclase-cGMP pathways [14,15]. It was confirmed that melatonin inhibits the cAMP and cGMP pathways and consequently decreases insulin release [2,8,14,15].…”
mentioning
confidence: 54%
“…Melatonin activates MT2 receptor that inhibits the second messenger cGMP and suppresses secretion of insulin through pancreatic β-cells (49,50 tially turns on CREB and/or C/EBP (CCAAT enhancer-binding protein. The MT2-receptor also affects the second messenger cAMP in an inhibitory manner.…”
Section: Melatonin Signaling In Pancreatic β-Cellsmentioning
confidence: 99%